2018
DOI: 10.1007/s00268-018-4546-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Bacterobilia on Morbidity and Postoperative Management After Pancreatoduodenectomy: A Systematic Review and Meta‐analysis

Abstract: Bacterobilia is detected during almost every second PD and is associated with an increased rate of SSI. The microbiome from intraoperative bile and postoperative infectious sources match in ~50% of patients, providing the option of early administration of calculated antibiotics and the determination of resistance patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
44
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 71 publications
9
44
0
3
Order By: Relevance
“…Fong et al [26], demonstrating a close correlation between organisms cultured from perioperative bile sampling and those subsequently seen in cultures from SSIs, with gutderived organisms identified in the majority of cases. In a systematic review and meta-analysis, Müssle et al [27] noted a median incidence of bacterobilia of 58%, and that intraoperative bile cultures and postoperative infections correlated in around 50% of cases. Furthermore, Ohgi et al [28] studied 264 patients and found in a multivariable analysis that positive intra-operative bile cultures were associated with clinically important pancreatic fistulae.…”
Section: Discussionmentioning
confidence: 99%
“…Fong et al [26], demonstrating a close correlation between organisms cultured from perioperative bile sampling and those subsequently seen in cultures from SSIs, with gutderived organisms identified in the majority of cases. In a systematic review and meta-analysis, Müssle et al [27] noted a median incidence of bacterobilia of 58%, and that intraoperative bile cultures and postoperative infections correlated in around 50% of cases. Furthermore, Ohgi et al [28] studied 264 patients and found in a multivariable analysis that positive intra-operative bile cultures were associated with clinically important pancreatic fistulae.…”
Section: Discussionmentioning
confidence: 99%
“…15 The mortality of patients undergoing pancreatoduodenectomy that developed biliary infection was reported as 5.9% in a review article. 16 Compared with these data, our mortality rate of 13.5% (7/52) among patients carrying A hydrophila after pancreatoduodenectomy or hepatectomy with biliary reconstruction was quite high. Moreover, the clinical course of these patients was rapid, and most of them died within 3 days after the onset.…”
Section: Discussionmentioning
confidence: 60%
“…For population PK modeling, NONMEM 7.3 (Icon Development Solutions, Ellicott City, Maryland) was used and executed via PsN (V4.4.0 [2]). Interindividual variability was implemented on the structural PK parameters as follows:…”
Section: Population Pk Analysismentioning
confidence: 99%
“…Postoperative local infection after pancreas resection occurs in up to 20% of patients and may lead to potentially major complications. Patients at risk for infected fluid collections after pancreatic surgery are predominantly but not exclusively patients who were preoperatively treated for jaundice and received interventional bile duct stenting . Infections of peripancreatic fluid collections possibly contribute to postoperative complications such as pancreatic fistula formation, which is the strongest factor for postoperative morbidity after pancreas resection.…”
mentioning
confidence: 99%
See 1 more Smart Citation